In vivo mapping and assay of matrix metalloproteases for liver tumor diagnosis. Issue 10 (20th January 2016) - Chen, Yu-Feng; Hong, Jin; Wu, Dong-Yan; Zhou, Ying-Ying; D'Ortenzio, Mathew; Ding, Ya; Xia, Xing-Hua
Abstract : A fluorescent probe constructed by simultaneous modification of FITC-grafted peptide and thiolated mPEG on the surface of gold nanoparticles for in vivo mapping and assay of matrix metalloproteases. Abstract : To improve current cancer treatment efficacy, a method for early and accurate detection is of great importance, especially for cancer biomarkers with a specific theranostic target. Matrix metalloproteases (MMPs) are a family of endopeptidases that are highly expressed in various types of cancers and play an important role inmetastasis. To detect and locate over-expressed MMPs in vitro and in vivo, a fluorescent "off–on" nanoswitch (GNP- p -FITC/mPEG) has been developed by engineering the fluorescein isothiocyanate-labeled peptide ( p -FITC) and thiolated polyethyleneglycol monomethyl ether (HS-mPEG, molecular weight 2000 Da) on the surface of gold nanoparticles (GNPs). The p -FITC contains a MMP preferential cleavage site and HS-mPEG is used to improve the stability and biocompatibility of the nanoswitch in vivo . The nanoswitch has a very low background signal and displays sensitive response to compound enzymes (containing MMP-2, MMP-4, and MMP-9 that may contribute to MMPs activity) either in vitro or in vivo . As a result of using GNPs, the nanoswitch has enhanced cellular internalization with HepG2 cells due to the endocytosis process as well as improved tumor penetration performance due to its small-size-induced enhanced permeability and retention (EPR). Furthermore, the biocompatibility and tumor targeting ability of the nanoswitch are established by its cytotoxicity with HepG2 cells and distributions in normal organs and tumor tissues. The simple preparation process, the complete fluorescence quenching, and the effective fluorescence recovery (about 50-fold intensity) makes the present MMP-responsive nanoswitch an accurate diagnosis probe for mapping MMPs and evaluating the tumor development both in vitro and in vivo .